Proceedings of the 12th IEEE Mediterranean Electrotechnical Conference (IEEE Cat. No.04CH37521) 2004
DOI: 10.1109/melcon.2004.1348226
|View full text |Cite
|
Sign up to set email alerts
|

On-line stator winding fault diagnosis in induction generators for renewable generation

Abstract: Abstract-Renewable generation systems are increasing its presence in electrical power systems. For this reason, it is more important than ever to count with reliable and secure generation systems. In this way, the use of on-line diagnostic techniques in the maintenance schemes can be useful. This paper is about on-line condition monitoring in induction generators for small hydro stations and wind farms. In particular, stator winding fault diagnosis is analyzed. Currently, there are diagnostic techniques that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…When scanning the available literature, it has been found that fault detection and diagnosis techniques are mainly arranged for inter-turn stator faults and stator or rotor asymmetries [20][21][22][23][24]. In all these works, authors are just applying wellestablished techniques to induction generators.…”
Section: A Electrical System (Dfig) Condition Monitoringmentioning
confidence: 99%
“…When scanning the available literature, it has been found that fault detection and diagnosis techniques are mainly arranged for inter-turn stator faults and stator or rotor asymmetries [20][21][22][23][24]. In all these works, authors are just applying wellestablished techniques to induction generators.…”
Section: A Electrical System (Dfig) Condition Monitoringmentioning
confidence: 99%
“…A combination of wavelet and power-spectral-density techniques for the detection of shorted turn faults in induction motors has been reported in [8]. Although, condition monitoring is normally done for induction motors [9], and it can also be carried out for induction generators as well [10].…”
Section: Indexmentioning
confidence: 99%
“…Some of these factors are the rigidity of the foundation of the test motor and the accuracy of the shaft alignment. The motors must have a firm and rigid foundation to eliminate soft foot problems and to reduce vibration [10].…”
Section: Indexmentioning
confidence: 99%
“…For small induction machines, the stator winding insulation degradation is one of the major causes [11], [21][22][23].…”
Section: A Wind Generators Failure Mode Analysismentioning
confidence: 99%